Initial experience with a new distal intermediate and aspiration catheter in the treatment of acute ischemic stroke: clinical safety and efficacy - Stampfl, Sibylle; Kabbasch, Christoph; Müller, Marguerite; Mpotsaris, Anastasios; Brockmann, Marc; Liebig, Thomas; Wiesmann, Martin; Bendszus, Martin; Möhlenbruch, Markus Alfred (Journal of neuroInterventional surgery, 2016)
Purpose To describe our initial experience with the novel 5 F SOFIA (Soft Torqueable catheter Optimized For Intracranial Access) intermediate and aspiration catheter for endovascular treatment of patients with acute ischemic stroke. Methods A retrospective review was performed in three centers of prospectively collected data of all stroke patients who underwent endovascular therapy using the SOFIA catheter. Patients were enrolled between November 2013 and December 2014. The primary endpoint of the study was accessibility of the thrombus with the SOFIA catheter. As a secondary endpoint, the study assessed recanalization success (Thrombolysis In Cerebral Infarction (TICI) ≥2b). Clinical presentation on admission and discharge was also documented. In addition, catheter- and procedure-related complications (particularly thromboembolic complications) were recorded. Results The SOFIA catheter was used in 115 acute stroke procedures. In 110 cases (96%) the catheter could be advanced to the occlusion site. After mechanical thrombectomy, successful recanalization (TICI ≥2b) was documented in 86.9%. There were no complications related to positioning of the catheter. Distal thrombus migration into a new vascular territory occurred in three patients following thrombectomy with a stent retriever (2.6%). The mean NIH Stroke Scale (NIHSS) score on admission was 16.8±6 and at discharge the mean NIHSS score was 8.2±7.7. Sixteen patients died. Conclusions The SOFIA catheter is a safe and efficient catheter for endovascular stroke therapy.
Published Online First 29 May 2015
Gesehen am 22.03.2018